PENGARUH RASIO HUTANG JANGKA PANJANG (LTDTER), RASIO PERPUTARAN PERSEDIAAN (ITO) DAN RASIO MARJIN LABA BERSIH (NPM) TERHADAP PERTUMBUHAN LABA PADA PERUSAHAAN SEKTOR PERTAMBANGAN YANG TERDAFTAR DI BURSA EFEK INDONESIA (BEI) PERIODE 2014-2018 - Anggereti Ang; Evelyn chen; Vivia cins (Universitas Gorontalo, 2020)
Abstract The objective of the study is to test and analyze the effect of Long Term Debt to Equity, Inventory Turnover and Net Profit Margin on Profit Growth of Mining Sector Companies listed in The Indonesia Stock Exchange in The Period of 2014-2018. The research method in this objective is used a quantitative research method with quantitative descriptive research type. The research populations were all companies listed in the Indonesia Stock Exchange consisting on 42 companies. The reach samples were 12 companies with sample technique using the Purposive Sampling technique. The research data were then analyzed using multiple linear regression analyze. The F-testing showed that F-count > F-table = 7,932 > 2,77 with significant level 0,000 < 0,05 indicating that Long Term Debt to Equity, Inventory Turnover and Net Profit Margin had significant effect on Profit Growth of Mining Sector Companies listed in The Indonesia Stock Exchange in The Period of 2014-2018. The result of testing showed that the value of T-count > T-table = 4,396 > 2,00324 with significant level 0,000 < 0,05 showing that partially, Long Term Debt to Equity have a significant effect on Profit Growth of Mining Sector Companies listed in The Indonesia Stock Exchange in The Period of 2014-2018. The result of testing showed that the value of T-count < T-table = 1,290 < 2,00324 with significant level 0,202 > 0,05 showing that partially, Inventory Turnover did not have a significant effect on Profit Growth of Mining Sector Companies listed in The Indonesia Stock Exchange in The Period of 2014-2018. Therefore, The result of testing showed that the value of T-count < T-table = 1,744 < 2,00324 with significant level 0,87 > 0,05 showing that partially, Net Profit Margin did not have a significant effect on Profit Growth of Mining Sector Companies listed in The Indonesia Stock Exchange in The Period of 2014-2018. The results of the determination coefficient analyze acquired from the value of Adjusted R² was 0,261, meaning that the variation in that Long Term Debt to Equity, Inventory Turnover and Net Profit Margin was 26,1% and the remaining 73,9% were explained by other variables. Keywords: Long Term Debt to Equity, Inventory Turnover, Net Profit Margin and Profit Growth